2021
DOI: 10.1111/jth.15327
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of coagulation, endothelial function, and fibrinolysis in critically ill patients with COVID‐19: A single‐center prospective longitudinal study

Abstract: Background: Immunothrombosis and coagulopathy in the lung microvasculature may lead to lung injury and disease progression in coronavirus disease 2019 .We aim to identify biomarkers of coagulation, endothelial function, and fibrinolysis that are associated with disease severity and may have prognostic potential. Methods:We performed a single-center prospective study of 14 adult COVID-19(+) intensive care unit patients who were age-and sex-matched to 14 COVID-19(−) intensive care unit patients, and healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 83 publications
9
60
2
Order By: Relevance
“…In this study, we found that plasma levels of sTM are higher in COVID-19 patients who died, suggesting that endothelial dysfunction contributes to poor outcome. These findings are consistent with a single-center study of hospitalized COVID-19 patients that showed that elevated levels of sTM predicts inhospital mortality ( 42 , 45 ). We also found that the predictive power of sTM is greater when using the most recent ICU plasma samples compared with the day 1 samples (Supplemental Table 3, http://links.lww.com/CCX/A861 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that plasma levels of sTM are higher in COVID-19 patients who died, suggesting that endothelial dysfunction contributes to poor outcome. These findings are consistent with a single-center study of hospitalized COVID-19 patients that showed that elevated levels of sTM predicts inhospital mortality ( 42 , 45 ). We also found that the predictive power of sTM is greater when using the most recent ICU plasma samples compared with the day 1 samples (Supplemental Table 3, http://links.lww.com/CCX/A861 ).…”
Section: Discussionsupporting
confidence: 91%
“…COVID-19 patients had similar levels as non-COVID-19 sick controls, and ICU-admitted patients had lower values compared to ward patients [10]. ICU COVID-19 patients had lower levels compared to ICU non-COVID-19 patients [11].…”
Section: Plasminogenmentioning
confidence: 81%
“…Since this discovery, 7 the importance of endothelial activation and dysfunction in COVID-19 has been intensively pursued. 8 , 18 , 23 , 26 More recently, increased markers of vascular inflammation, 27 oxidative stress, 28 EndoMT, 29 coagulation (D-dimer and plasminogen activator inhibitor-1), 15 , 30 immunothrombosis, 31 angiogenesis, 15 altered endothelial cell metabolism (glycolysis), 32 glycocalyx disruption 33 have been observed in patients with COVID-19 or SARS-CoV-2 spike protein treated endothelial cells (reviewed in ref. 9 ).…”
Section: Discussionmentioning
confidence: 99%